Demostración experimental de los fenómenos de consolidación y licuefacción en suelos típicos de Bogotá D.C. (2023)
In order to perform the experimental demonstration of consolidation, settlement and liquefaction phenomena in typical soils of the city of Bogota and their response to the load provided. The characterization of the materials was developed, from which a scale model was built (1:100) with soils formed from Guamo sand and kaolin, related in different proportions and stratified in the model, to be affected by conventional structures in Bogotá D.C. From 40 years ago and buildings with current requirements, in a time of 8 weeks. The properties of the aggregates compared with the available theory were calculated, being able to argue settlements for current structures of up to 9 meters, evidencing the vulnerability to differential settlements, damage to neighboring structures and possible liquefaction. Finalizing with the development of teaching methods of "consolidation, settlements and liquefaction" for the subject of Geotechnics 1 of the Antonio Nariño University. Concluding with an efficient presentation of real phenomena at scale size (1:100) and definition of high impact variables, such as clays and pore pressure, water table and possible liquefaction